Carrot or Stick? The Evolution of Reciprocal Preferences in a Haystack Model - Herold, Florian (American Economic Review, 2012)
We study the evolution of both characteristics of reciprocity: the willingness to reward and the willingness to punish. First, both preferences for rewarding and preferences for punishing can survive provided that individuals interact within separate groups. Second, rewarders survive only in coexistence with self-interested preferences, but punishers either vanish or dominate the population entirely. Third, the evolution of preferences for rewarding and the evolution of preferences for punishing influence each other decisively. Rewarders can invade a population of self-interested players. The existence of rewarders enhances the evolutionary success of punishers, who then crowd out all other preferences. (JEL C71, C72, C73, D64, K42)